Empirical Analysis of Return to Distance Higher Education in Different Disciplines - Li, Fengliang; Wang, Liang (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
Few empirical studies have analyzed the return to distance higher education in different academic disciplines. This study used quantitative methods, data from a nationwide survey, and Mincerian earnings function to analyze the return to distance higher education among different disciplines in China’s labor market. Results were compared with the return to face-to-face higher education and showed that the returns to face-to-face higher education were higher than those to distance higher education. Returns to the disciplines of economics and management were at a high level in both face-to-face and distance education; returns to the disciplines of literature, as well as education and law, were at a low level in both face-to-face and distance education. The returns to the disciplines of science and engineering were higher in face-to-face education than in distance education. This paper proposes several recommendations. Adults who do not have higher education degrees should invest in distance higher education to obtain considerable monetary returns, particularly in the disciplines with higher returns such as management and economics. China’s distance education institutions should improve the quality of teaching in science and engineering education and find ways to provide high-quality experimental teaching practices. At the same time, they should scale back on instruction of literature, as well as education and law.